Interactive Relationships Between Sex‐Related Alcohol Expectancies and Delay Discounting on Risky Sex. (18th February 2016) - Celio, Mark A.; MacKillop, James; Caswell, Amy J.; Mastroleo, Nadine R.; Kahler, Christopher W.; Barnett, Nancy P.; Colby, Suzanne M.; Operario, Don; Monti, Peter M.
Abstract : Background: Sex‐related alcohol expectancies reflect the degree to which a person believes alcohol will affect her or his sexual behavior. Sex‐related alcohol expectancies have been found to be predictors of drinking in sexual situations and engagement in risky sexual behavior after drinking. However, less is known about individual characteristics that may moderate these associations. Building upon recent evidence that steep delay discounting is associated with alcohol‐related sexual risk taking, this study aimed to test the hypothesis that the associations between sex‐related alcohol expectancies and alcohol‐related sexual risk taking would be stronger among individuals who discount delayed rewards more steeply. Methods: The current sample comprised 126 Emergency Department patients ( M age  = 27.37; 55% male) who reported high‐risk alcohol use and sexual behavior during the past 3 months. Sex‐related alcohol expectancies were assessed in 3 behavioral domains: increased riskiness, decreased nervousness, and enhanced sexuality. Results: All 3 expectancy domains were associated with quantity and frequency of alcohol use, as well as percentage of alcohol‐related condomless sex. Delay discounting moderated 2 of these relationships, such that the associations between expectancies for alcohol‐induced sexual risk taking and the enhancement of sexuality and percentage of alcohol‐related sexual risk‐taking were significantly stronger in individuals who exhibited steeper delay discounting. Conclusions: These findings suggest that individuals who both discount delayed rewards more steeply and hold strong sex‐related alcohol expectancies are a particularly high‐risk population. Such individuals may benefit from a combination of novel preventive strategies targeting sex‐related alcohol expectancies and impulsive decision making. Abstract : Results from this study on alcohol‐related sexual risk behavior in heavy drinking Emergency Department patients suggest that the expectancy that alcohol increases sexual riskiness is positively associated with engagement in alcohol‐related condomless sex with non‐steady partners, but only among individuals who discount delayed rewards more steeply. This study provides a novel perspective on the conditional role of expectancies in alcohol‐related sexual risk taking, and demonstrates how behavioral economics can help elucidate the association between alcohol and sexual risk behavior.